On natural coalgebra decompositions of tensor algebras and loop suspensions - Selick, Paul, 1950- (Memoirs of the American Mathematical Society ;, 2000)
Introduction Natural coalgebra transformations of tensor algebras Geometric realizations and the proof of Theorem 1.3 Existence of minimal natural coalgebra retracts of tensor algebras Some lemmas on coalgebras Functorial version of the Poincare-Birkhoff-Whitt theorem Projective $k(S_n)$-submodules of Lie$(n)$ The functor $A^{min}$ over a field of characteristic $p>0$ Proof of Theorems 1.1 and 1.6 The functor $L^′_n$ and the associated $k(Σ_n)$-module $Lie^′(n)$ Examples References.